Mechanism of deactivation processes of excited iron(III) thiocyanato complexes with benacen-type ligands (International Journal of Photoenergy)
The complexes [Fe(4-R-benacen)( CH 3 OH )(NCS)], where 4-R-benacen 2 − are tetradentate open-chain N , N ′ -ethylenebis(4-R-benzoylacetoneiminato) N 2 O 2 -ligands (R=H, Cl, Br, OCH 3 ), are redox stable in the dark in methanolic solutions. Irradiation of the complexes into intraligand and/or ligand-to-metal charge-transfer bands induces a series of photophysical and photochemical deactivation processes leading to Fe(II) and CH 2 O as final products in a 2 : 1 molar ratio. Formation of polystyrene containing bonded NCS group when irradiating the complexes in the presence of styrene monomer used as a radical scavenger indicates that the primary photoreduction of Fe(III) to Fe(II) is accompanied by the oxidation of NCS − ligand to • NCS radical. 4-R-benacen-ligands behave as an innocent moiety virtually not participating in the photoinduced redox processes. The quantum yield of Fe(II) formation φ Fe ( II ) decreases significantly with increased wavelength of the incident radiation, and is slightly influenced by the peripheral groups R of the 4-R-benacen-ligands.